Prototipo de riego automatizado para la producción de rosas usando la lógica difusa. - Hidalgo Aguaisa, Bryan Giovanny (2021)
Throughout these years, technology has transformed irrigation systems, with the aim of obtaining satisfactory results with respect to the optimization of water, time and, in turn, labor. The automation of an irrigation system is preferably applied to drip irrigation, since this technique is widely used in greenhouse rose crops, avoiding the generation of stagnant water or puddles. The automated irrigation system that allows water optimization is one that is based on fuzzy logic as an artificial intelligence (AI) technique, since it is the best alternative when it comes to monitoring environmental factors such as relative humidity or humidity of the soil, since it allows making decisions similar to what human beings do